Mycoplasma bovis Infections Occurrence, Pathogenesis, Diagnosis and Control, Including Prevention and Therapy - Dudek, Katarzyna; Szacawa, Ewelina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book presents the most important issues related to infections with Mycoplasma bovis, an etiological agent of many disorders in cattle, such as bronchopneumonia, mastitis, arthritis, otitis, keratoconjunctivitis, meningitis, and endocarditis. It consists of one review and eight research articles that discuss lung local immunity in experimental M. bovis pneumonia, antimicrobial susceptibility of M. bovis isolates, aspects related to M. bovis antibody testing, new data on the efficacy of seminal extender in M. bovis, as well as the importance of imported bull examination for this pathogen.